2022
DOI: 10.18261/nkt.25.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Finnish cultural policy as public funding: Regime view across policy domains

Abstract: Sakarias Sokka works as a senior researcher at CUPORE. His research interests include history and institutionalization of cultural policy, theoretical approaches to cultural policy, participation in culture, governing and governance of culture, art policies, and art and culture funding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…According to Paulsson and Macheridis (2022), who also concurs with Makhetha (2015) and Wu (2022), government policies are the result of a combination of systematic forces, political processes, institutional influences, rivalry among groups, elite preferences, belief in or advocacy of change through small steps, and rational planning (Fischer et al, 2015;Deygers and Vanbuel, 2022). Whatever decisions the government agrees on will fall under this (Kharel and Kharel, 2020;Jakonen and Sokka, 2022). Simeon (1976) concluded that policies are the climax of a complicated negotiation process and the outcome of several modest judgments made by decision-makers.…”
Section: Underpinnings Of Government Policymentioning
confidence: 94%
“…According to Paulsson and Macheridis (2022), who also concurs with Makhetha (2015) and Wu (2022), government policies are the result of a combination of systematic forces, political processes, institutional influences, rivalry among groups, elite preferences, belief in or advocacy of change through small steps, and rational planning (Fischer et al, 2015;Deygers and Vanbuel, 2022). Whatever decisions the government agrees on will fall under this (Kharel and Kharel, 2020;Jakonen and Sokka, 2022). Simeon (1976) concluded that policies are the climax of a complicated negotiation process and the outcome of several modest judgments made by decision-makers.…”
Section: Underpinnings Of Government Policymentioning
confidence: 94%
“…From the cultural policy perspective, cultural policy structure in Finland composes a rather stable, organised, and institutionalised system for the implementation of public policy (Jakonen and Sokka, 2022). At national level the structure of Finnish cultural policy consists of multiple government institutions, quasi-autonomous non-governmental organisations and interest organisations.…”
Section: Methodology Contextmentioning
confidence: 99%
“…At national level the structure of Finnish cultural policy consists of multiple government institutions, quasi-autonomous non-governmental organisations and interest organisations. The Ministry of Education and Culture (MEC) is responsible for the statutory art and cultural policy (see e.g., Kangas, 2001;Luonila et al, 2022, p. 48;Jakonen and Sokka, 2022). The state allocates subsidies to municipalities to produce cultural services with the aim of achieving a decentralisation of cultural policy implementation at the municipal level (Kangas, 2001, p. 65-66).…”
Section: Methodology Contextmentioning
confidence: 99%
“…These characteristics of Finnish cultural policy and funding have enabled professional artists and their organizations to have a relatively strong and influential position in cultural governance (Häyrynen 2018;Kangas 2003). However, this situation has recently been challenged by several factors: 1) the creative economy discourse in cultural policy emphasizing the economic importance of culture; 2) the entrepreneurialization of cultural work and its subjects; 3) institutional arrangements diminishing the autonomy of arts councils and increasing emphasis on strategic cultural policy; 4) the crisis management of the COVID-19 pandemic highlight the entrepreneurial and business side of cultural work (Jakonen & Pyykkönen 2023). All in all, based on these factors, it can be claimed that the power relations of different institutions in the field of culture are in the constant flux, and the 'economization' of culture seems to be strong tide at the moment (e.g., Hylland et al 2024;Jakonen & Pyykkönen 2023;Luonila et al 2022).…”
mentioning
confidence: 99%